Measurement of the inclusive J/ ψ polarization at forward rapidity in pp collisions at √s=8 TeV - Acharya, S.; Torales-Acosta, F.T.; Adamovã, D.; Adolfsson, J.; Aggarwal, M.M.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahn, S.U.; Aiola, S.; Akindinov, A.; et al. (Springer Science and Business Media, LLC, 2018)
We report on the measurement of the inclusive J/ψ polarization parameters in pp collisions at a center of mass energy √s = 8 TeV with the ALICE detector at the LHC. The analysis is based on a data sample corresponding to an integrated luminosity of 1.23 pb−1. J/ψ resonances are reconstructed in their di-muon decay channel in the rapidity interval 2.5 < y < 4.0 and over the transverse-momentum interval 2 < pT < 15 GeV/c. The three polarization parameters (λθ , λϕ, λθϕ) are measured as a function of pT both in the helicity and Collins-Soper reference frames. The measured J/ψ polarization parameters are found to be compatible with zero within uncertainties, contrary to expectations from all available predictions. The results are compared with the measurement in pp collisions at √s = 7 TeV.
Keywords: Physics; Rapidity; Particle physics; Lambda; Helicity; Large Hadron Collider; Muon; Polarization (electrochemistry); Tevatron; Nuclear physics; Quantum mechanics; https://purl.org/pe-repo/ocde/ford#1.03.03